2019
DOI: 10.1111/1462-2920.14535
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function and resilience to desiccation of methanogenic microbial communities in temporarily inundated soils of the Amazon rainforest (Cunia Reserve, Rondonia)

Abstract: Summary The floodplain of the Amazon River is a large source for the greenhouse gas methane, but the soil microbial communities and processes involved are little known. We studied the structure and function of the methanogenic microbial communities in soils across different inundation regimes in the Cunia Reserve, encompassing nonflooded forest soil (dry forest), occasionally flooded Igapo soils (dry Igapo), long time flooded Igapo soils (wet Igapo) and sediments from Igarape streams (Igarape). We also investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 78 publications
(109 reference statements)
2
18
0
Order By: Relevance
“…It is likely that those microbes may present protection against oxidative stress, as already reported for methanogens (Angle et al, 2017; Lyu, Shao Akinyemi, & Whitman, 2018). According to Hernández et al (2019), the abundance of methanogens could be an indication of the flooding history of the Amazon floodplain. In a microcosm experiment, the authors observed the survival of the methanogenic populations to short, but not to long periods of desiccation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that those microbes may present protection against oxidative stress, as already reported for methanogens (Angle et al, 2017; Lyu, Shao Akinyemi, & Whitman, 2018). According to Hernández et al (2019), the abundance of methanogens could be an indication of the flooding history of the Amazon floodplain. In a microcosm experiment, the authors observed the survival of the methanogenic populations to short, but not to long periods of desiccation.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have attempted to describe these communities (Conrad, Klose, Claus & Enrich-Prast, 2010; Conrad et al, 2011; Ji et al, 2016; Sawakuchi et al, 2016). Recently, using a microcosm experiment, Hernández et al (2019) showed that methanogens are present in high abundance in Amazonian floodplain sediments regardless of the incubation conditions, while their abundance in upland forest soils increases only upon anaerobic incubation. Nevertheless, to date, there was no effort to characterise the seasonal dynamics of the methanogenic and methanotrophic groups in situ .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we expected that more frequently drained soil environments exhibit smaller population changes than permanently flooded environments upon drainage or permanently dry environments upon flooding. We distinguished four categories: (1) permanently flooded lake sediments [ 69 , 70 ]; (2) annually flooded rice field soils or river floodplains [ 71 , 72 , 73 ]; (3) irregularly flooded soils (rice crop rotation) [ 74 , 75 , 76 ]; and (4) upland soils (including desert soils) [ 39 , 62 , 72 , 73 , 74 , 77 ]. We checked the potential of CH 4 production, the abundance of bacterial and archaeal microbiota, and the community composition of methanogenic archaea and (fermenting) bacteria.…”
Section: Oxygen Sensitivity and Microbial Populations In The Soil mentioning
confidence: 99%
“…The relative insensitivity of the methanogens to O 2 is consistent with the observations that dry and occasionally flooded soil environments were dominated by methanogens belonging to the genera Methanosarcina and Methanocella , which both belong to the O 2 -tolerant class II [ 68 ]. Methanosarcina and Methanocella species also increased in relative abundance after desiccation of permanently or frequently flooded soil environments, which, however, also contained O 2 -sensitive methanogens of class I (e.g., Methanosaetaceae , Methanobacteriales ) [ 71 , 73 ]. Hence, the abundance and composition of methanogen communities was consistent with theoretical expectations concerning O 2 sensitivity.…”
Section: Oxygen Sensitivity and Microbial Populations In The Soil mentioning
confidence: 99%
“…Alluvial plains are environments adapted to variations in water level, and it seems that microbial communities can be adapted to these fluctuations and remain in a state of latency until the next flood. Hernández et al [61] demonstrated that in Amazon forest soils the propensity to produce CH 4 (at the laboratory) was best observed in relation to the duration of the lag phase. Soils that were never flooded (dry forest) presented this phase for a longer time than sites that were permanently flooded.…”
Section: Influence Of Hydrology On Tropical Floodplainsmentioning
confidence: 99%